Олена Апанович та її внесок у дослідження та збереження могили Івана Сірка - Савченко, С. (Краєзнавство, 2018)
На матеріалах особового фонду Олени Апанович, які раніше не були в науковому обігу, розкривається діяльність відомої дослідниці козацтва по збереженню могили кошового Запорізької Січі Івана Сірка. This article is based on yet unpublished materials, inter alia from a personal fund of Olena Apanovych, it shows famous cossaks researcher’s activities on preservation of the grave of Zaporizhs’ka Sich otaman Ivan Sirko. Also, the documents from fund of Ukrainian Association of Historical and Cultural Memorials Preservation which are stored in Central State Archive of Highest Authorities and Management of Ukraine were found and analysed. The objective of the article is to show work and vision of O. Apanovych on the preservation of a famous figure of Ukrainian history. The article found that O. Apanovych were researching otaman’s grave in 1950th and later in 1960th while developing the Khortycya Reserve. She returned to preservation activities later at the end of 1980th to the beginning of 1990th while the expedition “Zaporizhs’ka Sich: destroyed and survived”. In 1960th Olena Apanovych had had an idea to move all Zaporizhs’ka Sich atamans’ graves to Khortycya where she was planning to create a national pantheon. At that time the idea was not realised. Later, while the “Reconstruction” she actualised the problem of Ivan Sirko’s grave preservation. This article in general analyses the influence of Olena Apanovych and her like-minded followers’ efforts towards the actualisation of preservation and popularisation of cossacks’ monuments. The article discovered that this work had very important social consequences for instance these activities had a significant impact on Ukrainian society in particular regarding rising of a national self-consciousness and preservation of national memory.